Evaluation of Drug Abuse by Hair Analysis and Self-Reported Use Among MSM Under PrEP: Results From a French Substudy of the ANRS-IPERGAY Trial. (15th April 2021) - Chas, Julie; Bauer, Rebecca; Larabi, Islam Amine; Peytavin, Gilles; Roux, Perrine; Cua, Eric; Cotte, Laurent; Pasquet, Armelle; Capitant, Catherine; Meyer, Laurence; Raffi, Francois; Spire, Bruno; et al.
Abstract : Background: We used the Agence nationale de Recherches sur le sida et les hépatites virales (ANRS)-IPERGAY trial to qualitatively and quantitatively measure drug use among men who have sex with men under preexposure prophylaxis using 2 different methods, to better understand and collectively respond to risky practices. Method: We included 69 volunteers of the ANRS-IPERGAY trial. We measured drug use by 2 methods: (1) drug detection by hair analysis and (2) reported drug use by self-reported drug consumption. Results: New psychoactive substances (NPS) and conventional drugs were detected in 53 of the 69 (77%) volunteers by hair analysis and in 39 of the 69 (57%) volunteers by questionnaires. On the 219 hair segments analyzed, the most commonly used drugs were cocaine in 47 of the 69 (68%), 3, 4-methylenedioxymethamphetamine/ecstasy in 31 of the 69 (45%), and NPS in 27 of the 69 (39%). On the 1061 collected questionnaires, the most commonly used drugs were cocaine in 31 of the 69 (45%), 3, 4-methylenedioxymethamphetamine/ecstasy in 29 of the 69 (42%), and NPS in 16 of the 69 (23%). Hair analysis detects more conventional drugs and/or NPS use ( P < 0.05). Drug use identified by hair was significantly associated with a higher number of sexual partners in the past 2 months ( P ⩽ 0.001), more often casual partners ( P ⩽ 0.001), condomless anal sex ( P ⩽ 0.005), hardcore sexual practices ( P ⩽ 0.001), a higher number of sexually transmitted infections, and chemsex ( P ⩽ 0.05). Conclusions: Self-report drug use by questionnaires remains the reference tool for harm reduction at the individual level because of its feasibility and low cost. However, hair analysis is more sensitive, objectively assessing consumption, and interesting to understand uses and to be able to collectively respond to risky practices with adapted messages.